Optimized CLT-RC frame connection for seismic retrofitting - Mehdipour, Zabih (2023)
Cross-laminated timber (CLT) panels have been used as a renovation solution to be adopted in existing masonry-infilled RC buildings, especially those which were designed based on old seismic codes. The connections through which the panels are attached to the RC frames have shown to provide the most contribution to the seismic behaviour of buildings, highly depending on the type of connections used. In this study, to investigate the effect of design procedures of bilinear RC-CLT connections on the dissipated energy and peak displacement of the retrofitted building, their optimum number, location, and mechanical properties, including elastic/inelastic stiffness and yielding displacement, are aimed to be found using genetic a algorithm in a one-bay one-story RC frame. Two structures, (1) a masonry-infilled frame strengthened by CLT panel and (2) a CLT-infilled frame, are used to take the effect of masonry infill into account for two optimization purposes, maximum energy dissipation and minimum structural drift. Results show that under different predefined levels of structural performance, different optimum bilinear curves are achieved. In a parallel study, concerning connectors’ arrangement, it was found that their horizontal distribution in beams, starting from the middle and moving to the corners, result in a much better response than a vertical distribution in columns.